Constitutive model of concrete under multi-axial stresses - Hu, Ou Er. (2008)
Based on the Triaxial Elasto-Plastic and Continuum Fracture Model, which was proposed by Maekawa (1993), a novel isotropic constitutive model, the Modified Triaxial Elasto-Plastic and Continuum Fracture Model is proposed in the present work to simulate the nonlinear behavior of concrete under triaxial cyclic loading by appropriately representing the damage, plasticity, and hysteresis.